Cohort profile: UK Millennium Cohort Study (MCS) - Connelly, Roxanne; Platt, Lucinda (International journal of epidemiology, 2014)
The UK Millennium Cohort Study (MCS) is an observational, multidisciplinary cohort study that was set up to follow the lives of children born at the turn of the new century. The MCS is nationally representative and 18 552 families (18 827 children) were recruited to the cohort in the first sweep. There have currently been five main sweeps of data collection, at ages 9 months and 3, 5, 7 and 11 years. A further sweep of data collection is planned for age 14 years. A range of health-related data have been collected as well as measures concerning child development, cognitive ability and educational attainment. The data also include a wealth of information describing the social, economic and demographic characteristics of the cohort members and their families. In addition, the MCS data have been linked to administrative data resources including health records. The MCS provides a unique and valuable resource for the analysis of health outcomes and health inequalities. The MCS data are freely available to bona fide researchers under standard access conditions via the UK Data Service (http://ukdataservice.ac.uk) and the MCS website provides detailed information on the study (http://www.cls.ioe.ac.uk/mcs).